Characteristics of Obstructive Sleep Apnea Patients With a Low Body Mass Index: Emphasis on the Obstruction Site Determined by Drug-Induced Sleep Endoscopy - Woo, Hyun-Jae; Lim, Jae Hyun; Ahn, Jae-Cheul; Lee, Yu Jin; Kim, Dong-Young; Kim, Hyun-Jik; Rhee, Chae-Seo; Won, Tae-Bin (Clinical and experimental otorhinolaryngology, 2020)
Objectives. This study aimed to elucidate the patterns of upper airway collapse in obstructive sleep apnea (OSA) patients with a low body mass index (BMI).Methods. We designed and conducted a retrospective cohort study. Consecutive patients diagnosed with OSA who underwent drug-induced sleep endoscopy (DISE) were included. Patients were classified into four groups according to their BMI. Age, sex, and polysomnography data were investigated. The patterns of upper airway collapse were characterized by the structures involved (soft palate, tongue base, lateral pharyngeal wall, and epiglottis). We compared the patterns of upper airway collapse in the supine and lateral decubitus position among the four BMI groups using the chi-square test and multivariate binary logistic regression analysis.Results. A total of 627 patients (male, 517; mean age, 47.6±12.8 years) were included, consisting of 45, 79, 151, and 352 patients who were underweight or lower normal-weight (defined as the low BMI group), upper normal-weight, overweight, and obese, respectively. Severity indicators of OSA, such as the overall apnea-hypopnea index and duration of SaO2 below 90%, were significantly lower in patients with a low BMI than in obese patients, while their average oxygen saturation was significantly higher. The most common obstruction site in the supine position was the tongue base in patients with a low BMI (100%), whereas this obstruction site was significantly less common in obese patients (54.8%). Tongue base obstruction was mostly relieved in the lateral position, with no discernible obstruction in 86.7% of the low BMI patients.Conclusion. Airway obstruction in OSA patients with a low BMI is mostly due to tongue base obstruction, which improves in the lateral position. These characteristics should be kept in mind when considering treatment options for this subgroup of OSA patients.